Mysterious helmet from Verden and its “link” with Tibetan helmets - KUBIK, Adam (Historia i Świat, 2017)
The article discusses a helmet that was published in 1914 in Zeitschrift für Historische Waffenkunde. It was possibly found by a German farmer during field works near the town of Verden in Lower Saxony. The helmet which was previously associated with the Saxons and dated between Migration Period and the reign of Charlemagne shows clearly relations with far Asian constructions. Additionally I discuss here another helmet in The Metropolitan Museum of Art, which seems to be a 20th century reworking that imitated the Verden helmet